Plasma Pharmacokinetics of Cannabidiol Following Oral Administration of Cannabidiol Oil to Dairy Calves - Meyer, Kelsey; Hayman, Kristen; Baumgartner, James; Gorden, Patrick J. (Frontiers in Veterinary Science, 2022)
Cannabidiol (CBD), the non-psychotropic component of cannabis, has drawn increased interest amongst some medical professionals for its potential therapeutic effects. Human and canine work has been done to describe CBD where it is already widely used, however, little is known about the effects of CBD in livestock species. The purpose of this descriptive study was to determine the pharmacokinetics (PK) of CBD in calves after a single oral exposure to CBD oil. Seven male Holstein calves received a single oral dose of 25 mg/mL CBD oil to achieve 5 mg/kg dose of CBD. Blood samples were collected for 48 (h) after dosing. The CBD geometric mean maximum concentration of 0.05 ug/mL was reached 7.5 h after administration. The geometric mean half-life was 23.02 h. Cannabidiol administered orally to cattle is slowly absorbed and has an extended elimination half-life compared to other species.